Kontroversi Etik Hakim Mahkamah Konstitusi pada Putusan Batas Usia Capres Cawapres: Pelanggaran Kode Etik dalam Perspektif UU MK dan UUD 1945 - Intan Sahwa (Jurnal Hukum Lex Generalis, 2025)
The Constitutional Court Decision Number 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates has raised an ethical controversy that shakes the integrity of the constitutional judiciary. This study discusses potential violations of the judicial code of ethics, conflicts of interest, and their implications for the principles of independence and impartiality as regulated in the Constitutional Court Law and the 1945 Constitution. The discussion results indicate deviations from the fundamental values of Sapta Karsa Hutama and the principle of constitutional justice, leading to a decline in public trust toward the Constitutional Court.